THE INFLUENCE OF FRAUD TRIANGLE UPON THE EXISTENCE OF FINANCIAL STATEMENT FRAUD - Lutfiana Hermawati; Murtanto Murtanto (Indonesian Management and Accounting Research, 2019)
This research is designed to find empirical evidence on the influence of fraud triangle factors upon the existence financial  statement fraud in Indonesian Listed companies. The research samples are 105 public companies consisting 42 fraud firms and 63 non fraud firms. Classification between fraud firm and non fraud firm uses the Eckel index.The result indicate that: first, the external pressure variable that proxied by debt, personal need variable that proxied by insiders’ stock ownership,and CEO’s education, and inefective monitoring variable taht proxied by unexistence antifraud program and training have positive significant influence to the existence of financial statement fraud. Second, the personal financial need variable taht proxied by CEO’s Tenure, the inefective monitoring variable that proxied by unexistence whistleblowing program, and rationalization variable that proxied by auditor change have negative significant to the existence of financial statement fraud. Third, simultaneously all independent variables have an influence to the existence of financial statement fraud. Keywords: financial statement fraud, income smoothing, fraud triangle.